(untitled) (KYAMC Journal, 2019)
Background: Hanging is the most common form of violent asphyxial death in our country. Typical and atypical variety of hanging depends on position of knot at the victim body. Objective: The objective of this study was to find out the position of knot of ligature material and relation of knot with the working hands in hanging cases along with socio demographical status of the study subjects. Materials and Methods: This retrospective study was conducted among 574 Autopsy cases of hanging victims at the Dhaka Medical College Morgue during the period January 2013 to December 2015. Results: Out of 574 cases, 159 (27.71%) were male and 415 (72.29 %) female. Among them 304(52.96%) were married and 270(47.04%) were unmarried. Most of the victims 269(46.86%) were from the age group 21- 30 years. Considering the knot, most were situated at right side of neck 281 (48.95%), followed by left side 235 (40.94%), at the nape of neck 50(8.71%) and in front of neck below chin 8(1.39%). Most of the study subjects were right handed. Dopatta (orna) was the commonest 237(41.28%) ligature material. 556 (96.86%) cases had some form of ligature mark in neck. Most of the victims 401(69.86%) hanged themselves at night. 545 body (94.95%) were recovered from inside the living rooms. 472 (82.23%) victims had complete suspension and 102 (17.77%) were cases of partial hanging. Conclusion: To reduce the number of suicidal hanging cases a well designed and comprehensive programme is needed, which will identify the causative factors and prevent of suicidal behaviors of affected persons. KYAMC Journal Vol. 10, No.-1, April 2019, Page 17-20